COOPERATION OF THE CUSTOMS ADMINISTRATION WITH GOVERNMENT ADMINISTRATION AUTHORITIES, LOCAL GOVERNMENT AND ECONOMIC SELF-GOVERNMENT - Laszuk, Mirosława (Ekonomia i Prawo. Economics and Law, 2013)
While carrying out its tasks, the Polish customs administration collaborates with many entities – government administration authorities, local government as well as economic self-government. Constant cooperation takes place mainly with authorities and institutions whose tasks are associated with tasks which are being realized by the customs administration. Cooperation with local and state administration bodies and the local government takes place to a lesser extent. This cooperation is of supportive character. Another type of cooperation is the cooperation with local governments. Its character is intensive. The result of this cooperation is the implementation of a number of facilities for entrepreneurs dealing with foreign commodity trading.